2022
DOI: 10.1111/gcb.16364
|View full text |Cite
|
Sign up to set email alerts
|

More future synergies and less trade‐offs between forest ecosystem services with natural climate solutions instead of bioeconomy solutions

Abstract: To reach the Paris Agreement, societies need to increase the global terrestrial carbon sink. There are many climate change mitigation solutions (CCMS) for forests, including increasing bioenergy, bioeconomy, and protection. Bioenergy and bioeconomy solutions use climate-smart, intensive management to generate high quantities of bioenergy and bioproducts. Protection of (semi-)natural forests is a major component of "natural climate solution" (NCS) since forests store carbon in standing biomass and soil. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…First, it is crucial to understand the type and extent of EPS when designing sustainable climate change mitigation policy. Second, policymakers can minimize EPS by regulating how and where mitigation options are implemented, thereby leveraging the moderating factors of EPS ( 63 , 64 ). Examples include the choice of feedstock for bioenergy, which can minimize several shifts, and placing photovoltaics on rooftops or in agri-voltaic systems, which can prevent or limit shifts to land use and biodiversity loss.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is crucial to understand the type and extent of EPS when designing sustainable climate change mitigation policy. Second, policymakers can minimize EPS by regulating how and where mitigation options are implemented, thereby leveraging the moderating factors of EPS ( 63 , 64 ). Examples include the choice of feedstock for bioenergy, which can minimize several shifts, and placing photovoltaics on rooftops or in agri-voltaic systems, which can prevent or limit shifts to land use and biodiversity loss.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a key insight from the ecosystem services management framework, and therefore multifunctionality, is the unavoidable trade-offs in benefit supply (Mazziotta et al, 2022;Morán-Ordóñez et al, 2020;Turkelboom et al, 2018;Vergarechea et al, 2023). Assessing the synergies and trade-offs of ecosystem services could provide a baseline for comparing alternative future scenarios and insights into potential policy and management outcomes (Bryan, 2013;Mouchet et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Heinonen et al (2018) also found that timber supply increased under climate change, except at the end of the century under the most severe scenario (RCP8.5) because very high temperatures and low soil water availability can limit forest growth. In addition, this increase in forest growth due to climate change might decrease yields of bilberry and cowberry as it is likely that forests will become too dense, leading to a decrease in wild berries production because of a reduction in sunlight reaching the understory vegetation (Mazziotta et al, 2022;Peura et al, 2016). et al, 2020), temperate (Gutsch et al, 2018;Thrippleton et al, 2021) and mountainous forests (Mina et al, 2017).…”
Section: The Potential Supply Of Es Mostly Increases Under Set Aside ...mentioning
confidence: 99%
“…On the other hand, rising temperature and vapor pressure deficit have mostly negative effects on forest demographic rates, but may have positive effects in cold and wet regions such as the boreal zone (McDowell et al, 2020). Moreover, several studies suggest negative impacts of climate change on the provisioning of non‐wood forest ES (Breshears et al, 2011; Elkin et al, 2013; Lindner et al, 2014; Mazziotta et al, 2022) and on the biodiversity these ecosystems host (e.g., Mazziotta et al, 2015; Virkkala, 2016). In boreal forests, the impact of climate change on ES depends on the specific service, as increasing temperatures have been projected to increase harvest‐ and carbon‐related services but decrease some cultural services such as winter sports (Holmberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation